On Question of “Analytical Article” Text Type - D. T. Dorzhieva (Научный диалог)
The question is raised about the type of text “analytical article.” The definition of the notion “type of text” is given. The place of analytical article in the system of journalistic genres is commented. Analytical article is considered in the framework of non-classical text classification, the differentiating criterion of which is the paradigm of thinking. The paradigm of thinking is understood as type of mentality typical to certain era, which corresponds to a certain type of mass text. These text types and trends of their development in connection with the change of paradigm of thinking in society are described. The author believes that this classification of text types allows for a fresh look at the genre of the article. A review of the text types most clearly correlated with the analytical article is made: persuasive text, pragmatic text, meaning deducing text. The author comes to the following conclusions. A distinctive feature of the meaning deducing text lies in its essential inderectiveness, while persuasive and pragmatic types of text are potentially manipulative. Persuasive and pragmatic types of text tend to have a certain effect on the addressee and to have a certain relevance to current events. The meaning deducing text enables the recipient to realize his/her right to free choice and independent opinion.